Bacterial Consortium for Improved Maize (Zea mays L.) Production - Oluwaseyi Samuel Olanrewaju (Microorganisms, 2019)
The ever-increasing human population is a major concern for food security. Maize is the third largest most important food crop. The major problems of cultivation arise from urbanization and land pollution. This reduces the amount of land available for agriculture. The use of chemicals in agriculture is not environmentally friendly. Thus, plant growth-promoting bacteria (PGPB) have been proposed as alternatives. This study aims to test the growth-promoting effect of maize inoculated with six indigenous PGPB isolates. These isolates were assayed for various biochemical and plant growth-promoting activities. They were also assayed for biocontrol activities. Based on the results, six isolates viz A1, A18, A29, NWU4, NWU14, and NWU198 were used to inoculate maize seeds. The inoculated seeds were tried out on the field. A randomized block design was used. PGPB used were in single, consortia of two, and three organisms. The length of the leaves, roots, and stem, plant height, numbers of leaves, and weight of 100 seeds were taken at the fourth and eighth weeks after planting. Microbial consortia increased growth parameters compared to single inoculant treatments. Thus, they can be of advantage in the eradication of low yield. They can also serve as reliable alternatives to chemical fertilizers.